Metabolic profiling of neurospheres derived from embryonic cerebral cortex Ts1Cje mouse model for down syndrome - Mohamed Seth, Eryse Amira (2019)
Down syndrome (DS) is a genetic disorder caused by triplication of human chromosome 21 (Hsa21) and is the most common cause of intellectual disability. Several studies have revealed proliferation deficits and higher proportion of glial cells compared to neurones in the brains of DS humans and mouse models, which were suggested to contribute to intellectual disability. While a vast majority of previous literature has been focused on the molecular aspects, current knowledge on metabolic dysregulations in neural stem and progenitor cells (NSPCs) derived from embryonic Ts1Cje mice is limited. Ts1Cje mouse model for DS has been indispensable in expanding our knowledge on the molecular and cellular mechanisms of the disorder. In this study, embryonic cerebral cortex of Ts1Cje and wild type (WT) mice were isolated at embryonic day 15.5 and cultured in the form of neurospheres. Biolog Phenotype MicroArray (PM) was employed to obtain metabolic profiles for the embryonic Ts1Cje and WT neurospheres. Four types of PM colourimetric assays pre-coated with 367 biochemical substrates, including oxidizable carbon and nitrogen sources, were utilised. Analysis of Biolog PM data using an established statistical pipeline revealed a significant decrease in utilisation of 17 substrates and a significantly higher utilisation of 6 substrates in the Ts1Cje neurospheres compared to the WT neurospheres. A prominent finding is the significantly decreased utilisation of glucose-6-phosphate (G6P) and α-D-glucose in the Ts1Cje neurospheres compared to WT. L-serine, and dipeptides containing histidine and isoleucine were also utilised significantly lower in Ts1Cje neurospheres, whereas glutamate-containing dipeptides were utilised significantly higher in Ts1Cje neurospheres compared to WT neurospheres. G6P is involved in two energy-producing pathways: pentose phosphate pathway (PPP) and glycolysis. To investigate whether intermediates of G6P metabolism can improve generation of the embryonic Ts1Cje neurospheres, neurospheres were supplemented with 6-phosphogluconic acid (6PG) and fructose-6-phosphate (F6P) and assessed after 6 days in vitro. The mean diameter of the embryonic Ts1Cje neurospheres was higher when supplemented with 2.0 mM of 6PG compared to no supplement, suggesting that supplementation with 6PG may rescue the effects of perturbed PPP in the embryonic Ts1Cje neurospheres. On the other hand, there was no significant difference between the Ts1Cje neurospheres supplemented with and without F6P, indicating that there are possibly no alterations in glycolysis. The enzyme activity of glucose-6-phosphate dehydrogenase (G6PDH), which catalyzes the catabolism of G6P in PPP, was also assessed. The G6PDH activity of Ts1Cje neurospheres was generally lower compared to WT neurospheres, but the difference was not statistically significant. Without supplementation of 6PG, G6PDH activity of the embryonic Ts1Cje neurospheres was found to be lower than that of the WT neurospheres. Meanwhile, increasing concentration of 6PG results in a larger difference in G6PDH activity between the Ts1Cje and WT neurospheres, although the differences were not statistically significant. Taken together, these data suggest that alterations in metabolic pathways, particularly PPP, may contribute to defects observed in NSPCs of embryonic Ts1Cje mice. Investigation on the metabolic properties of Ts1Cje embryonic NSPCs enhances our knowledge on underlying dysregulations in NSPCs during early brain development in DS, and may complement previous genomic, transcriptomic and proteomic studies on Ts1Cje mice.